تأثير استخدام اللعبة اللغوية "الكلمات المتقاطعة" على استيعاب الطلاب القواعد الإملائية (بحث تجريبي في الفصل الثاني المتوسط بالمدرسة الإسلامية المتوسطة الحكومية ليما فولوه باتو بارا) - Sinaga, Hana Khoirany; Zaky, Ahmad; Tumanggor, Ilham (ANWARUL, 2024)
Writing is one of the productive communication skills in the language. This is the process by which someone changes the language code from spoken language to written text. The writing skill has two divisions: calligraphy, dictation, and composition. Dictation is one of the important subjects in teaching the Arabic language. Hence, dictation is the basis for success in writing skill. Teaching dictation looks at how to write correct Arabic grammar. Dictation is considered a person's ability to write letters in the Arabic language. Dictation is a basic learning skill in writing that requires a special method to master it. The method used is the quantitative method with an experimental method design with a post-test. The design for this research is the true experimental design with the type of posttest method (posttest only control group). The researcher takes a sample of forty-eight students from the second semester of middle school. This number is divided into two groups, group A and group B, and the researcher takes these two groups because group A is the experimental group and group B is the control group. From this, the researcher makes 24 students in the experimental class and 24 students in the control class. As for analyzing the data using a statistical method, SPSS 18, and the population size was 56 and 48 people were sampled. The result on the effect of the crossword language game is the reciprocal hypothesis, that is, the result in the t-test is 4.51 greater, while the result in the t-table is 02.01063.